Effects of a weight-reduction program with orlistat on serum leptin levels in obese women: A 12-week, randomized, placebo-controlled study - Ozcelik, O; Dogan, H; Kelestimur, H (Excerpta Medica Inc, 2004)
Background: Leptin, which has been identified as an antiobesity hormone, regulates body weight by controlling food intake and energy expenditure via the hypothalamic-pituitary-gonadal axis. It appears that leptin may be an important factor in obesity management. Orlistat, a pancreatic lipase inhibitor, could reduce fat absorption and promote weight loss due to leptin metabolism. Objective: The purpose of this study was to investigate the effects of orlistat therapy on serum leptin levels. Methods: Obese women (body mass index [BMI], 30 kg/m(2)) aged 18 to 50 years were randomly assigned to receive 12 weeks of oral treatment with diet-orlistat (120 mg TID) (DO group) or diet-placebo (DP group). During the treatment period, patients were asked to eat a balanced diet of similar to1200 to 1600 kcal/d. Body composition was determined by bioelectrical impedance. Serum leptin levels were measured using radioimmunoassay at baseline and at study end. Results: A total of 24 patients entered the study; 14 patients (mean [SE] BMI, 37.7 [1.1] kg/m(2)) received orlistat and 10 patients (mean [SE] BMI, 39.4 [1.3] kg/m(2)) received placebo. Compared with baseline, mean percentages of loss of body weight and fat mass after 12 weeks of treatment were significant in the DO group (9.1% and 14.8%, respectively; both P = 0.001) and in the DP group (9.5% and 17.6%; both P = 0.005). The between-group differences were not statistically significant. Mean (SE) serum leptin levels also decreased significantly after treatment in the DO group (16.2 [1.2] vs 9.0 [1.0] ng/mL; P = 0.001) and in the DP group (19.3 [2.1] vs 9.7 [1.4] ng/mL; P = 0.005). The between-group difference was not statistically significant. Conclusions: In this study of obese women, orlistat treatment was associated with a similar decrease in body weight, fat mass, and serum leptin levels as placebo over a 12-week period. In this regard, short-term orlistat therapy may not provide an additional effect on serum leptin levels, and reduction in leptin levels were closely related to the decrease in fat mass. Copyright (C) 2004 Excerpta Medica, Inc.
Keywords: leptin; obesity; orlistat; pharmacotherapy